Magnetic Resonance Imaging of The Distal Radial Epiphysis Forensic Age Estimation in Living Individuals - Ekizoğlu, Oğuzhan; Hocaoğlu, Elif; İnci, Ercan (The Bulletin of Legal Medicine, 2017)
Objective: Determining forensic age is very important in legal and civil rights cases, particularly in those involving children and young adults. Although methods for performing such estimates have been developed and their reliability has been demonstrated, radiation exposure has become controversial. In recent years, magnetic resonance imaging (MRI) has been used in an attempt to protect patients from radiation exposure. The aim of this study is to evaluate usefulness of staging via magnetic resonance imaging of distal radial epiphysis in age estimation.Materials and Methods: In this study, 198 hand-wrists (patient age, 12–20 years) were retrospectively evaluated with MRI using the “distal radial epiphysis assessment method,” which was used previously by Dvorak to evaluate professional sportsmen.Results: The ages at which bony fusion occurs have been identified. Females reach stage 2 at 13 years, stages 3 and 4 at 14 years, stage 5 at 15 years, and stage 6 at 16 years, whereas males reach stages 2 and 3 at 14 years, stage 4 at 15 years, and stages 5 and 6 at 16 years.Conclusion: Although the non-ionizing Dvorak method of analyzing the distal radius epiphysis was successfully used for subjects aged 13–16 years, it failed to provide data about 17 and 18-year-olds. Thus, we need to develop a method for this age group and expand the applicable population.
Keywords: age estimation; age determination; distal radial epiphysis; magnetic resonance imaging